2021
DOI: 10.1002/ehf2.13548
|View full text |Cite
|
Sign up to set email alerts
|

Admission NT‐proBNP and outcomes in patients without history of heart failure hospitalized with COVID‐19

Abstract: Aims We examined the value of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) in patients admitted for coronavirus disease 2019 (COVID‐19) without prior history of heart failure (HF) or cardiomyopathy. Methods and results Retrospective cohort of consecutive adults ( N = 679; median age 59 years; 38.7% women; 87.5% White; 7.1% Black; 5.4% Asian; 34.3% Hispanic) admitted with documented COVID‐19 in an academic centre in Long Island, NY. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
14
0
5
Order By: Relevance
“…Myocardial injury with COVID-19 has been extensively reported, with rates widely varying depending upon the population studied. 4 The underlying causes are numerous and include but are not limited to myocarditis, 22 acute coronary syndrome (myocardial infarction type 1), 17 demand ischemia (myocardial infarction type 2), 25 , 32 , 33 , 34 , 35 multisystem inflammatory syndrome in children (MIS-C) and multisystem inflammatory syndrome in adults (MIS-A), 20 , 21 , 24 takotsubo/stress cardiomyopathy, 36 , 37 cytokine storm, 34 acute cor pulmonale resulting from macropulmonary or micropulmonary emboli, 23 , 25 myocardial injury from chronic conditions like pre-existing heart failure, 38 , 39 , 40 , 41 and acute viral infection unmasking subclinical heart disease. 38 Because 1 or more of these etiologies may coexist, it can sometimes be challenging to identify a specific underlying cause.…”
Section: Description Of Pathwaymentioning
confidence: 99%
“…Myocardial injury with COVID-19 has been extensively reported, with rates widely varying depending upon the population studied. 4 The underlying causes are numerous and include but are not limited to myocarditis, 22 acute coronary syndrome (myocardial infarction type 1), 17 demand ischemia (myocardial infarction type 2), 25 , 32 , 33 , 34 , 35 multisystem inflammatory syndrome in children (MIS-C) and multisystem inflammatory syndrome in adults (MIS-A), 20 , 21 , 24 takotsubo/stress cardiomyopathy, 36 , 37 cytokine storm, 34 acute cor pulmonale resulting from macropulmonary or micropulmonary emboli, 23 , 25 myocardial injury from chronic conditions like pre-existing heart failure, 38 , 39 , 40 , 41 and acute viral infection unmasking subclinical heart disease. 38 Because 1 or more of these etiologies may coexist, it can sometimes be challenging to identify a specific underlying cause.…”
Section: Description Of Pathwaymentioning
confidence: 99%
“…In a large Spanish cohort of COVID‐19 patients, NT‐proBNP was frequently elevated even in the absence of clinical criteria for the diagnosis of HF. Moreover, NT‐proBNP was independently associated with mortality after adjusting for relevant confounders, including chronic HF and acute HF 308–310 . Lassen et al .…”
Section: Comorbiditiesmentioning
confidence: 99%
“…The results were consistent across age, sex, and race, and independent of coronary artery disease or hypertension, except for a stronger mortality signal with elevated NTproBNP in women. In conclusion, in patients with COVID-19 and without a history of heart failure, a high NT-proBNP level at admission is associated with higher mortality and health care resource utilization [7] . Another conducted retrospective, single-center cohort study, showed that the median age of the patients was 61 years (IQR, 47-69), and 39 (43.0%) of them were men.…”
Section: Bnp and Nt-probnpmentioning
confidence: 85%